The European Large-Area ISO Survey (ELAIS): the final band-merged catalogue - Rowan-Robinson, M; Lari, C; Perez-Fournon, I; Gonzalez-Solares, E; La Franca, F; Vaccari, M; Oliver, S; Gruppioni, C; Ciliegi, P; Heraudeau, P; Serjeant, S; Efstathiou, A; et al. (2004)
We present the final band-merged European Large-Area ISO Survey (ELAIS) Catalogue at 6.7, 15, 90 and 175 μm, and the associated data at U, g′, r′, i′, Z, J, H, K and 20 cm. The origin of the survey, infrared and radio observations, data-reduction and optical identifications are briefly reviewed, and a summary of the area covered and the completeness limit for each infrared band is given. A detailed discussion of the band-merging and optical association strategy is given. The total Catalogue consists of 3762 sources. 23 per cent of the 15-μm sources and 75 per cent of the 6.7-μm sources are stars. For extragalactic sources observed in three or more infrared bands, colour-colour diagrams are presented and discussed in terms of the contributing infrared populations. Spectral energy distributions (SEDs) are shown for selected sources and compared with cirrus, M82 and Arp220 starburst, and active galactic nuclei (AGN) dust torus models. Spectroscopic redshifts are tabulated, where available. For the N1 and N2 areas, the Isaac Newton Telescope ugriz Wide Field Survey permits photometric redshifts to be estimated for galaxies and quasars. These agree well with the spectroscopic redshifts, within the uncertainty of the photometric method [∼ 10 per cent in (1 + z) for galaxies]. The redshift distribution is given for selected ELAIS bands and colour-redshift diagrams are discussed. There is a high proportion of ultraluminous infrared galaxies (log 10 of 1-1000 μm luminosity L ir > 12.22) in the ELAIS Catalogue (14 per cent of 15-μm galaxies with known z), many with Arp220-like SEDs. 10 per cent of the 15-μm sources are genuine optically blank fields to r′ = 24: these must have very high infrared-to-optical ratios and probably have z > 0.6, so are high-luminosity dusty starbursts or Type 2 AGN. Nine hyperluminous infrared galaxies (L ir > 13.22) and nine extremely red objects (EROs) (r - K > 6) are found in the survey. The latter are interpreted as ultraluminous dusty infrared galaxies at z ∼ 1. The large numbers of ultraluminous galaxies imply very strong evolution in the star formation rate between z = 0 and 1. There is also a surprisingly large population of luminous (L ir > 11.5), cool (cirrus-type SEDs) galaxies, with L ir - L opt > 0, implying A v > 1.